New and little known mollusks from ancient chemosynthetic environments - Kiel, Steffen; Campbell, Kathleen A.; Gaillard, Christian (Zootaxa, 2010)
Twelve mollusk species from late Jurassic to Oligocene cold seep deposits are described and illustrated. Nine of them are new, two have already been named, two new genera are introduced, and one species is described only in open nomenclature. Puncturella (sensu lato) mcleani sp. nov. and Fissurella (sensu lato) bipunctata Stanton, 1895 are the only confirmed fissurellids in fossil cold seeps. The sutilizonid Triassurella goederti sp. nov. is similar to the modern ventinhabiting Sutilizona and the Late Triassic shallow-water reef-inhabitant Triassurella carnica. A smooth, late Jurassic neritid is the oldest neritid from fossil seeps and probably represents an independent neritid radiation into the seep environment, without close phylogenetic connection to the modern Bathynerita. The four new abyssochrysoid caenogastropods Humptulipsia macsotayi, Hokkaidoconcha novacula, Paskentana anistratenkorum, and P. umbilicata significantly extend the stratigraphic and geographic ranges of these apparently seep-restricted genera. Four bivalves are described, including the new modiomorphid Caspiconcha rubani from the early Cretaceous and the new bathymodioline Bathymodiolus (s.l.) palmarensis from the Oligocene. Among the lucinids, the oldest seep-inhabiting lucinid (late Jurassic) is described as Beauvoisina carinata gen. et sp. nov.; the new genus Cubatea is introduced for an Oligocene lucinid from Cuba. It is suggested that Caspiconcha, Paskentana, and hokkaidoconchids constitute the core of a seeprestricted fauna that inhabited seeps worldwide from (at least) late Jurassic to early Cretaceous time. These taxa are, at the family level, phylogenetically unrelated to the modern vent and seep fauna.